Digital marketing analysis on the consumer decision-making process of millennials and Gen Z generation groups on the TikTok application - Estetia Adistsany Salwanisa; Ira Wikartika (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2023)
This study investigates the impact of digital marketing on consumer behaviour in purchase decision-making among Millennials and Gen Z generations. The study employs convenience sampling with twenty respondents through a qualitative and exploratory research method. The research examines consumer behaviour based on their purchasing experiences. Findings reveal that digital marketing changes how consumers recognize problems, search for information, and evaluate products. User-generated content, such as reviews and recommendations, significantly influences consumers' information search process. Additionally, consumers tend to utilize comparative methods when assessing products. The study provides valuable insights for marketing practitioners in designing effective strategies to influence consumer behaviour in the digital era. A deep understanding of the role of digital marketing is crucial in achieving successful marketing goals in an increasingly connected digital landscape.